Who gets to learn in a pandemic? Exploring the digital divide in remote learning during the COVID-19 pandemic in Nigeria - Azubuike, Obiageri Bridget; Adegboye, Oyindamola; Quadri, Habeeb (International journal of educational research open, 2021)
This study investigates the digital divide in access to remote learning for children in Nigeria, as a result of the COVID-19 pandemic. The data used in this study is from a survey conducted by The Education Partnership (TEP) Centre and the Nigerian Economic Summit Group (NESG), which sampled 557 students and 626 parents living in Nigeria. From the survey, we found: a relationship between the socioeconomic status and the digital divide in accessing remote learning, significant differences in students’ access to remote learning opportunities during the pandemic, and significant differences in access to digital tools between students in government schools and their private school counterparts. We also found a statistically significant association between parental level of education and the ability to support children's remote learning during the pandemic.